Enhancing preschoolers’ Language and Literacy Development in Costa Rica: A Family-Based Intervention Using Dialogic Reading and Reminiscing - Carmiol Barboza, Ana María (2025)
Using a randomized controlled design in Costa Rica, this study examined the effects of a family intervention to promote early language and literacy development through dialogic reading and elaborative conversations about the past. Seventy-six caregivers and their preschool-age children were assigned to one of three experimental groups: dialogic reading, elaborative reminiscing, or an active control group, where caregivers learned about healthy eating habits. Caregivers in each group participated in an intervention that consisted of an in-person training session and follow-up text messages for 15 weeks. Children’s oral language and code-related skills were assessed before and after the intervention. Changes in vocabulary from intervention books, story comprehension, and decoding skills differed across groups, with the dialogic reading group showing greater gains than the reminiscing and control groups. The results suggest that dialogic reading at home can effectively promote early language and literacy development in preschool-age children in Costa Rica when incorporated into family language and literacy interventions.